1982
DOI: 10.1007/bf00377932
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Salmonella mutagenicity assay and determination of polycyclic aromatic hydrocarbons in workplaces exposed to petroleum pitch and petroleum coke

Abstract: Workplaces of an Italian carbon electrode factory, exposed to petroleum pitch and petroleum coke, were studied using a coupled chemical and biological approach to evaluate occupational mutagenic/carcinogenic hazards. Analytical procedures for the determination of polycyclic aromatic hydrocarbons (PAH) and Salmonella/microsome mutagenicity tests (with TA98 and TA100 strains) were performed on both industrial ingredients (pitch and coke) and airborne particulate matter of the working environment, after fractiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…8,9 Thus, an argument could be made that a cause-effect relationship is plausible. On the other hand, the Salmonella data also suggest that the entrained volatile material might not be bioavailable under normal physiological conditions, 7 but rather requires vigorous extraction procedures in order for its activity to be expressed. 8,9 It should also be noted that PAC-containing substances also produce systemic effects including liver enlargement, reduced spleen weights, and changes in hematological parameters.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Thus, an argument could be made that a cause-effect relationship is plausible. On the other hand, the Salmonella data also suggest that the entrained volatile material might not be bioavailable under normal physiological conditions, 7 but rather requires vigorous extraction procedures in order for its activity to be expressed. 8,9 It should also be noted that PAC-containing substances also produce systemic effects including liver enlargement, reduced spleen weights, and changes in hematological parameters.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, several carcinogenic or cocarcinogenic constituents have been discovered in these products. A number of authors have shown the presence of polycyclic aromatic hydrocarbons (PAHs), some of which are known to be carcinogenic or cocarcinogenic (Bingham et al, 1979;IARC, 1983), in working operations with mineral oils, tar, pitch, and bitumens (Guerin et al, 1978;Hueper and Payne, 1960;Kipling and Waldron, 1976;Lindstedt and Sollenberg, 1982;Monarca et al, 1982Monarca et al, ,1984Monarca et al, ,1987Peake and Parker, 1980;Thayer et al, 1983;Thony et al, 1975). In particular, PAHs are concentrated in the highest boiling point distillates and in the solid residues obtained from petroleum processing.…”
Section: Introductionmentioning
confidence: 96%
“…In particular, PAHs are concentrated in the highest boiling point distillates and in the solid residues obtained from petroleum processing. For instance, petroleum pitch is heavily enriched in PAHs (Gammage, 1983;Guerin, 1978;Monarca et al, 1982). Several authors have recently studied the mutagenic properties of these petroleum products (Guerin et al, 1981;Hermann et al, 1980aHermann et al, , 1980bMonarca et al, 1982Monarca et al, , 1984Monarca et al, , 1987Pasquini and Monarca, 1983;Peake and Parker, 1980).…”
Section: Introductionmentioning
confidence: 97%
“…Although approximately 500 substances are used in the manufacture of rubber [4], and most of these are …”
Section: Introductionmentioning
confidence: 99%
“…Rubber factory workers Pulmonary function Forced expiratory volume Suspended particulate matter Benzo(a)pyrene Radiological abnormalities known to be capable of causing acute or chronic respira tory effects [4][5][6][7], there is a need for detailed information on the effect of the size of suspended particles, or work place benzo(a)pyrene concentration, on lung function in rubber manufacturing workers. For this reason, the present study was carried out to examine two measures of lung function, namely the forced vital capacity (FVC; the volume of air expelled by a maximum voluntary expira tion after a maximum voluntary inspiration) and the forced expiratory volume in one second (FEVi ; that part of the FVC expired in the 1st second of expiration) in workers in a rubber manufacturing factory.…”
Section: Introductionmentioning
confidence: 99%